Long-non-coding RNA AK001058: A genetic biomarker in cisplatin sensitivity of non-small-cell lung carcinoma: LncRNA AK001058 and NSCLC - Deng, Yongjun; Li, Huimin; Liu, Chao; Xia, Xiuqiong; Lv, Yanhua; Zhang, Dandan; Liang, Jianping (Cellular and Molecular Biology, 2023)
Previous evidences have shown that lncRNA AK001058 serves as an oncogene. This study aims to elucidate the expression characteristic of AK001058 in NSCLC samples, and its potential influence on the malignant progression and cisplatin resistance of NSCLC. Relative levels of AK001058 and IGF2 in NSCLC and non-tumoral tissues were detected by qRT-PCR. Proliferation inhibition rate and migratory rate in DDP-induced SPC-A1 and A549 cells were examined by CCK-8 and Transwell assay, respectively. Subsequently, DDP-resistant SPC-A1 and A549 cell lines were generated, and the role of AK001058 in affecting their cell phenotypes was determined. Using dual-luciferase reporter assay, the binding relationship between AK001058 and IGF2 was verified. Their co-regulation on DDP-resistant NSCLC cells was finally explored via rescue experiments. AK001058 was upregulated in NSCLC samples. The proliferative rate was dose-dependently and time-dependently declined in DDP-induced SPC-A1 and A549 cells. Cisplatin induction upregulated AK001058 in NSCLC cells, and attenuated migratory potential. Transfection of sh-AK001058 reduced proliferative and migratory rates in SPC-A1/DDP and A549/DDP cells. IGF2 was the downstream target binding AK001058, which was lowly expressed in NSCLC samples. AK001058 upregulation in NSCLC reduces cisplatin sensitivity and promotes malignant progression by negatively regulating IGF2, leading to cisplatin resistance.